Effect of Feeding Isotoma longiflora Leaf Extract with Ethanol Solvent on Performance and Small Intestine Histomorphology of Broiler: Pengaruh Pemberian Ekstrak Daun Kitolod (Isotoma longiflora) dengan Pelarut Etanol terhadap Peforma dan Histomorfologi Usus Halus Broiler - Dani, Muhammad; Kususiyah; Kebat, Purnama Sari; Marlita, Refi; Bilyaro, Woki; Azis, Arif Rahman (BPFP Universitas Bengkulu, 2024)
This study aims to determine the effect of giving kitolod leaf extract with ethanol solvent on growth performance and histomorphology of broiler small intestine. The research design used in this study was a complete randomized design (CRD) with 4 treatments and 5 replicates. Each replicate used 10 DOC. The treatment details are as follows; P0 = drinking water without ethanol extract of kitolod leaves; P1 = drinking water + 1% ethanol extract of kitolod leaves; P2 = drinking water + 2% ethanol extract of kitolod leaves; P3 = drinking water + 3% ethanol extract of kitolod leaves. Parameters observed were broiler growth performance (feed consumption, body weight gain, and feed conversion ratio) and small intestine histomorphology (villi height and krypta depth). The results showed that ration consumption was 1410.39-468.97 g/head/28 days, body weight gain was 1855.69-1904.05 g/head/28 days, feed conversion ratio was 1.30-1.32, villi height was 775.75-907.59 µm and kripta depth was 218.94-244.67 µm. Giving kitolod leaf extract with ethanol solvent has not been able to improve the growth performance and histomorphology of broiler small intestine.